PENGEMBANGAN INDUSTRI KELAPA SAWIT SEBAGAI PENGHASIL ENERGI BAHAN BAKAR ALTERNATIF DAN MENGURANGI PEMANASAN GLOBAL - Masykur . (REFORMASI, 2013)
Palm oil is an agricultural commodities that are popular today. Indonesia as the country with the world's largest exporter of palm oil with Malaysia. Riau Islands is a port exporting Crude Palm Oil (CPO) in the city of Dumai, Indonesia's largest palm oil exporter and the biggest producer of palm oil in Indonesia.The palm oil industry is a industry sectors that result high foreign exchange to the country of Indonesia.So the palm Industrialization done first Indonesia due to the high global demand for Crude Palm Oil (CPO) as a source of vegetable oil. Growth will demand CPO within 5 (five) years, the average growth of 9.92%. Second, a new energy source that the function substitute petroleum reserves dwindling and its natural resources are non-renewable. One of these alternative energy is the energy of biofuel which is the main feedstock crude palm oil (Crude Palm Oil). Alternative energy is a renewable biofuel, to overcome the crisis of fuel oil (BBM) in Indonesia, can strengthen the availability of fuel, and environmentally friendly, thereby reducing the production of greenhouse gases. Third, the tools to reduce and even prevent and tackle global warming is palm oil. The role of palm oil is one of which was the residence of flora and fauna.